Toward System-Wide Implementation of Patient-Reported Outcome Measures: A Framework for Countries, States, and Regions - Ernst, Sophie-Christin Kornelia; Steinbeck, Viktoria; Busse, Reinhard; Pross, Christoph (Value in health, 2022)
This study aimed to develop a framework facilitating (1) the maturity assessment of healthcare systems regarding patient-reported outcome measure (PROM) implementation and (2) the comparison of different healthcare systems’ PROM implementation levels to guide discussions and derive lessons for regional, state-level, and national PROM initiatives. Guided by the grounded theory methodology, a PROM healthcare system implementation framework was developed following multiple steps. Based on interviews with 28 experts from 12 countries and a literature review, a framework was drafted and refined through 29 additional validation interviews. The resulting framework comprises 5 implementation stages along 7 dimensions. Implementation stages range from “first experimentation” to “system-wide adoption and a vibrant ecosystem.” The dimensions are grouped into patient-reported outcome (PRO) measurement and PRO utilization, the former with the dimensions “scope and condition coverage,” “metric and process standardization,” and “tools and information technology–based solutions” and the latter with “patient empowerment and clinical decision support,” “reporting and quality improvement,” and “rewarding and contracting.” The “culture and stakeholder involvement” dimension connects both groups. Although a concerted implementation approach across dimensions can be observed in advanced countries, others show a more uneven adoption. The framework and its preliminary application to different healthcare systems demonstrate (1) the importance of coherent progress across complementing dimensions and (2) the relevance of PROM integration across clinical specialties and care sectors to strengthen patient-centered care. Overall, the framework can facilitate dialogues between stakeholders to analyze the current PROM implementation status and strategies to advance it. •Healthcare system stakeholders currently lack a framework providing guidance on how to assess, compare, and improve patient-reported outcome measure (PROM) implementation in different countries amid the fragmented PROM landscape.•This study develops and validates a comprehensive framework to assess a healthcare system’s maturity regarding the collection and utilization of PROMs and to conduct a status-quo analysis or cross-country, cross-state, or cross-region comparisons.•The framework and its preliminary application stress the importance of (1) PROM integration across specialties and care sectors to strengthen patient-centered care and (2) coherent progress across the framework’s patient-reported outcome measurement and patient-reported outcome utilization dimensions.